Introducing climate change into the biochemistry and molecular biology curriculum. Issue 2 (24th August 2020) - Jakubowski, Henry V.; Bock, Nicholas; Busta, Lucas; Pearce, Matthew; Roston, Rebecca L.; Shomo, Zachery D.; Terrell, Cassidy R.
Abstract: Our climate is changing due to anthropogenic emissions of greenhouse gases from the production and use of fossil fuels. Present atmospheric levels of CO2 were last seen 3 million years ago, when planetary temperature sustained high Arctic camels. As scientists and educators, we should feel a professional responsibility to discuss major scientific issues like climate change, and its profound consequences for humanity, with students who look up to us for knowledge and leadership, and who will be most affected in the future. We offer simple to complex backgrounds and examples to enable and encourage biochemistry educators to routinely incorporate this most important topic into their classrooms.